Fractional extraction of coconut oil by supercritical fluid extraction and its application as cocoa butter substitute in chocolate production - Abdul Halim, Halimatun Sa'adiah (2017)
Cocoa butter is generally produced from coconut oil (CNO) and palm kernel oil which has similar physical characteristics as cocoa butter (CB). However, CNO contains high lauric acid which is different from CB and can be reduced by fractional extraction using Supercritical Fluid extraction (SFE). Therefore, aim of this study was to produce CBS from coconut oil (CNO) by fractional extraction with Supercritical Fluid Extraction (SFE). The objectives of this study were: i) to determine the effects of different pressures and temperatures on extraction of CNO and CNO fractions by SFE, ii) to determine the effects of different level of coconut oil fractions substituted CB in milk chocolate. CNO was extracted with SFE at four different pressures (27.6, 34.5, 41.4, 48.3MPa) and temperatures of 60 ºC and 80 ºC. Then, the selected parameter conditions were applied for fractional extraction of CNO with SFE. The selected F-CNO was applied as CBS in milk chocolate production at different level. The properties of milk chocolates which include melting profile, hardness, rheology, consumer acceptance and bloom stability were analysed to determine the effects of F-CNO substitute in milk chocolate. The yield of CNO extracted at the highest pressure, 48.3 MPa and temperature, 80 ºC was significantly (p<0.05) higher (63.1%) and significantly (p<0.05) lower lauric acid (44.75%) compared to others. The pressure at 48.3 MPa and temperature of 80 ºC was selected as SFE operating parameter for the fractional extraction of the CNO. The fractional extraction give four different fractions, F1, F2, F3 and F4. F1 had significantly highest (p<0.05) yield (48.9%). The F4 contained significantly (p<0.05) lowest short and medium chain fatty acids while highest long chain fatty acids compared to F1, F2 and F3. F4 also had significantly (p<0.05) highest Tonset (24.2 ºC) and Tendset (33.6 ºC) which were close to CB. The solid fat content of F4 was 0% at temperature between 35 ºC to 40ºC. Therefore, F4 was selected as the potential fraction of CNO (F-CNO) to be applied as CBS due to close properties to CB. The F-CNO (F4) was applied in milk chocolate to substitute cocoa butter at 1.5% (chocolate A), 3.0% (chocolate B) and 4.5% (chocolate C) compared with control chocolate (without F-CNO). The different levels of F-CNO substituted in milk chocolate resulted in different triglyceride composition which affected the melting profile, hardness and rheology. The melting profile of the milk chocolates A, B and C decreased significantly (p<0.05) as level of F-CNO added increased. The initial melting point of the milk chocolate decreased from 30.72 ºC to 28.98 ºC while the end melting point decreased significantly from 40.31 ºC to 36.36 ºC. The hardness of the milk chocolate significantly (p<0.05) decreased from control, followed by chocolate A, then, chocolate B and finally chocolate C. The rheology of the milk chocolate decreased significantly (p<0.05) when level of F-CNO added increased. Sensory evaluation shown consumer panelists (52%) significantly most preferred (p<0.05) the chocolate C which contain 4.5% F-CNO in terms of glossiness (6.72) taste, (6.92) and overall acceptability (6.60) compared to control (glossiness=5.57, taste=5.70 and overall=5.57). During bloom stability study, the whiteness index (WI) of control chocolate was higher compared to chocolate with F-CNO. Based on these findings, the F-CNO has the potential to be applied as CBS in chocolate based product with high stability.